1986
DOI: 10.1073/pnas.83.24.9719
|View full text |Cite
|
Sign up to set email alerts
|

Human beta-melanocyte-stimulating hormone revisited.

Abstract: It is generally accepted that human 13-melanocyte-stimulating hormone (h.BMSH) does not normally exist in humans but was merely an artifactually generated 22-amino acid peptide corresponding to a lipotropin (LPH) fragment (residues 35-56). We examined whether the shorter 18-amino acid peptide hBMSH-(5-22) could be detected in some human tissues. MATERIALS AND METHODSTissue Collection. The following tumors were surgically obtained from five patients with ectopic ACTH syndrome: tumors E1-E4 were bronchial carci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1

Year Published

1989
1989
2018
2018

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 22 publications
0
24
1
Order By: Relevance
“…These studies also revealed two unexpected findings: (a) the testis POMC RNA is shorter than the pituitary POMC mRNA, being -800 nt long (25,26). We (38). Contrary to the previous RIA, h(3LPH and hI3MSH showed 100% cross-reactivity, and hflMSH5-22 had no cross-reactivity.…”
Section: Introductioncontrasting
confidence: 50%
“…These studies also revealed two unexpected findings: (a) the testis POMC RNA is shorter than the pituitary POMC mRNA, being -800 nt long (25,26). We (38). Contrary to the previous RIA, h(3LPH and hI3MSH showed 100% cross-reactivity, and hflMSH5-22 had no cross-reactivity.…”
Section: Introductioncontrasting
confidence: 50%
“…Our findings provide additional support for a more critical role of ␤MSH than of ␣MSH in the control of human energy balance (12,17,18). Because ␤MSH is present in the human hypothalamus (25) and seems to have higher affinity for the hMC4R (26), it is likely to be the more physiologically relevant endogenous ligand for the hMC4R (when compared with ␣MSH). The obese phenotype associated with the POMC M, male, F, female; age at obesity onset is defined as age with BMI above the 97th percentile; Ins T0, fasting insulinemia; Gly T0: fasting glucose; HOMA, homeostasis model assessment index defined as (fasting insulin level ϫ fasting glucose level) divided by 22.5; TG, triacylglycerol; Chol, total cholesterol; ?, data not available; ND, not determined.…”
Section: Discussionmentioning
confidence: 64%
“…Subsequently, the peptide was considered to be an artifact of procedure and did not exist in humans. However, more recently, naturally occurring ␤-MSH-octadecapeptide has been identified in human hypothalamus (Bertagna et al, 1986). The peptide corresponds with the ␥-LPH (41-58) sequence.…”
Section: Melanocortin Peptidesmentioning
confidence: 99%